The degree of possessing information literacy skills and its relationship to the use of digital information resources among postgraduate students at the faculty of education/university of Damascus. (Journal of Hama University, 2021)
The study aimed to identify the degree of information literacy and its relationship to the use of digital information sources for graduate students in the Faculty of Education at the University of Damascus. To achieve the goal of the study, the researcher designed two tools: The first scale of technological literacy consists of (35) items distributed on three axes: access to information, organization Information, information evaluation, and the second measure is the use of digital information sources consisting of (20) items. The descriptive approach was used and research tools were applied to (77) graduate students at the Faculty of Education at the University of Damascus in the second semester of the academic year 2018/2019.The researcher reached the following results: The degree of information literacy has reached a total level for graduate students (2.73) which is an average degree, and the degree of using digital information sources (2.95), and the results also showed a relationship between the use of digital information sources and the degree of information literacy, as the results showed There were no statistically significant differences between the mean scores of the sample individuals about the degree of informational literacy due to the gender variable, while the results showed that there were statistically significant differences between the mean scores of the sample individuals about the degree of informational literacy attributed to the variable of the scientific level in favor of the Ph.d students. The research presented a set of proposals, such as: Providing students in universities with the skills of informational literacy, due to the nature of their studies that depend on research and investigation in the knowledge and digital age and increasing interest in designing training programs to provide students with informational literacy skills.